Pictet–Spengler-Based Multicomponent Domino Reactions to Construct Polyheterocycles - Hu, Jun-Duo; Huang, Li-Liang; Feng, Huang-Di (Pharmaceutical Fronts, 2023)
The Pictet–Spengler reaction is one of the important methodological arsenals in synthetic and medicinal chemistry, acting as an amenable tool for preparing tetrahydroisoquinoline, tetrahydro-β-carbolines, polycyclic skeletons, and value-added products. More than 100 years after its initial discovery, the Pictet–Spengler reaction's response has not withdrawn from the stage, but it has once again become the focus of attention with new features. The review summarizes recent advances in Pictet–Spengler-based multicomponent reactions from 2007 to 2022, including three-component and four-component Pictet–Spengler cyclization reactions in the presence of metal catalysts, organocatalysts, biological enzyme catalysts, and so on. These Pictet–Spengler-based multicomponent protocols provide an atom-/step economic approach for the synthesis of a library of new chemical entities.
Keywords: Pictet–Spengler reaction; multicomponent reactions; domino reactions; cyclization; heterocycles